Breakthrough of Organic Electroluminescence Efficiency of Photoluminescence in Frequency Domain - HUANG, JIN-ZHAO; LI, SHI-SHUAI; FENG, XIU-PENG; WANG, PEI-JI; ZHANG, ZHONG (Asian Journal of Chemistry, 2010)
In this paper, a new way is proposed to confirm that the organic electroluminescence efficiency can exceed the 25 % limitation of that of photoluminescence in frequency domain. In present experiment, the spectra shows two characteristic emission bands and the high and low energy emission bands are due to singlet and triplet excited states. The triplet emission has longer lifetime than that of singlet emission and the emission intensity of short lifetime changes (increase and decrease) more dramatic than that of long lifetime with the changing frequency. So, it may be concluded that the 25 % limitation is not perfect and can be exceeded in the frequency domain at a given frequency.